2014
DOI: 10.1108/et-01-2013-0005
|View full text |Cite
|
Sign up to set email alerts
|

Examining the mediating role of learning engagement, learning process and learning experience on the learning outcomes through localized real case studies

Abstract: Purpose -The purpose of this paper is to understand the impact of real, localized case studies on students' learning engagement, the learning process and learning experience and the role of such case studies in influencing students' learning outcomes. Design/methodology/approach -Data were collected from 400 undergraduate students through an online questionnaire immediately after discussion of the case in Business Information Systems classes. Student learning from the case study was measured by two components … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
5

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 54 publications
0
12
0
5
Order By: Relevance
“…Course-related interactions were found to be positively related with student engagement (Umbach and Wawrzynski, 2005). With its focus on promoting the interaction among students, discussion cases via case knowledge and case perception significantly increased students’ EAE (Nkhoma et al, 2014). Once students immerse into the world of a case, they are more likely to get excited, motivated and emotionally engaged.…”
Section: Interactivity and Emotional Engagement (Eae)mentioning
confidence: 99%
See 1 more Smart Citation
“…Course-related interactions were found to be positively related with student engagement (Umbach and Wawrzynski, 2005). With its focus on promoting the interaction among students, discussion cases via case knowledge and case perception significantly increased students’ EAE (Nkhoma et al, 2014). Once students immerse into the world of a case, they are more likely to get excited, motivated and emotionally engaged.…”
Section: Interactivity and Emotional Engagement (Eae)mentioning
confidence: 99%
“…Discussion cases, through open and interactive discussions, were among the most effective methods to encourage critical thinking in business education (McEwen, 1994). On the other hand, a study found an insignificant relationship between learning engagement and learning outcomes (both group and individual outcomes) since the discussion and analysis were not graded (Nkhoma et al, 2014). Therefore, due to mixed results, it would be worthwhile to examine the effect of EAE on learning outcomes.…”
Section: Engagement and Learning Performancementioning
confidence: 99%
“…Tujuan utama dalam taksonomi Bloom mengenai desain hasil belajar peserta didik adalah untuk melengkapi siswa dalam mencapai tiga klasifikasi utama ini atau domain (Tetteh, 2015). Ada banyak yang dapat mempengaruhi hasil dalam pembelajaran seperti kualitas pengajaran, lingkungan, fasilitas pembelajaran, metode, model dalam pembelajaran, kepuasan belajar (Jungjoo, 2011) (Nkhoma & Sriratanaviriyakul, 2014).…”
Section: Tinjauan Pustaka Hasil Belajarunclassified
“…Furthermore, case-based learning was found helpful for undergraduate nutrition education, which was designed for students bearing on the theoretical frameworks of phenomenology and Bloom's Taxonomy (Harman et al, 2015). However, case studies might need to be designed appropriately and be instructed cautiously along with proper learning activities (Nkhoma, Sriratanaviriyakul, Pham, & Lam, 2014). The utilisation of case-based learning in this study is expected to promote self-study and collaborative learning, which will improve cognitive skills, academic achievement and interpersonal skills.…”
Section: Literature Reviewmentioning
confidence: 99%